Molecularly Engineered Covalent Organic Frameworks for Hydrogen Peroxide Photosynthesis. Issue 19 (25th February 2022) - Kou, Mingpu; Wang, Yongye; Xu, Yixue; Ye, Liqun; Huang, Yingping; Jia, Baohua; Li, Hui; Ren, Jiaqi; Deng, Yu; Chen, Jiahao; Zhou, Ying; Lei, Kai; et al.
Abstract: Synthesizing H2 O2 from water and air via a photocatalytic approach is ideal for efficient production of this chemical at small‐scale. However, the poor activity and selectivity of the 2 e − water oxidation reaction (WOR) greatly restricts the efficiency of photocatalytic H2 O2 production. Herein we prepare a bipyridine‐based covalent organic framework photocatalyst (denoted as COF‐TfpBpy) for H2 O2 production from water and air. The solar‐to‐chemical conversion (SCC) efficiency at 298 K and 333 K is 0.57 % and 1.08 %, respectively, which are higher than the current reported highest value. The resulting H2 O2 solution is capable of degrading pollutants. A mechanistic study revealed that the excellent photocatalytic activity of COF‐TfpBpy is due to the protonation of bipyridine monomer, which promotes the rate‐determining reaction (2 e − WOR) and then enhances Yeager‐type oxygen adsorption to accelerate 2 e − one‐step oxygen reduction. This work demonstrates, for the first time, the COF‐catalyzed photosynthesis of H2 O2 from water and air; and paves the way for wastewater treatment using photocatalytic H2 O2 solution. Abstract : A bipyridine‐based covalent organic framework photocatalyst (COF‐TfpBpy) showed excellent activity for H2 O2 photosynthesis with a solar‐to‐chemical conversion efficiency of 0.57 % at 298 K and 1.08 % at 333 K. The photocatalytic process involves a 2 e − water oxidation and 2 e − oxygen reduction from water and air. The photocatalytic H2 O2 solution can be directly used for Rhodamine B degradation and sterilization of E. coli .